Monitoring Information System of Regional Potential Management Through Village Owned Business Entity (BUMDES) in Banyuwangi - Millati, Izzato; Hilmin, Siti Nur; Rohma, Minadatur; Romauli, Nelly; Khoiruwnia, Fadhilah; Listiani, Trisma (UNEJ e-Proceeding, 2021)
This study uses an exploratory qualitative approach which is a research that is more focused in the process where researchers must interact directly with research subjects in the research location, data obtained through interviews, observation, and documentation. The researcher uses an exploratory point of view because the researcher does not have an overview of the research concept that will be obtained in depth so that more in-depth information/data collection is needed, then formulates a proposal in the form of an integrated hospital service accounting information system design. In addition, this study uses the concept of Action Research, because in this study we describe, interpret and explain a social situation for the problems that occur, and formulate solutions, with the hope that the results of our research can help carry out work more effectively and efficiently. In this study, the researcher wants to try to reveal in depth information about the existing BUMDes management system in Banyuwangi in order to further analyze what improvements or developments must be made to increase its effectiveness and efficiency. The goal to be achieved from this research is to create an effective regional potential management system to improve the economy of rural communities during the pandemic. The results of this study can be used as reference material and references that can be used by managers of the economic sector in an effort to improve the economy of rural communities, especially during the pandemic and can be used as discussion material or reference for further research on accounting information systems design. Keywords: Accounting Information System, Accounting Information System Design, Regional Potential, BUMDes